2016
DOI: 10.2147/ppa.s94275
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with diet barriers in patients with poorly controlled type 2 diabetes

Abstract: BackgroundThe study was conducted to investigate the diet barriers perceived by patients with poorly controlled type 2 diabetes and examine the associations between diet barriers and sociodemographic characteristics, medical condition, and patient-centered variables.MethodsSecondary subgroup analyses were conducted based on the responses of 246 adults with poorly controlled type 2 diabetes from a multicenter, cross-sectional study. Diet barriers were captured by the Diet Barriers subscale of the Personal Diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 57 publications
7
35
0
Order By: Relevance
“…Besides, failures in the provision of information were associated to low adherence to drug treatment, lack of regular physical exercise, and consumption of foods with high sugar content. These findings are coherent with previous studies which mentioned that not having received or understood the information about portions and the frequency of meals may be associated with low adherence to diet in diabetic patients (Ranasinghe et al, 2015;Cheng et al, 2016;Parajuli, Saleh, Thapa & Ali, 2014). Thence, it is important that the information provided to the diabetic patient has clear recommendations for self-care, expressed in a kind of language that the patient may fully understand.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Besides, failures in the provision of information were associated to low adherence to drug treatment, lack of regular physical exercise, and consumption of foods with high sugar content. These findings are coherent with previous studies which mentioned that not having received or understood the information about portions and the frequency of meals may be associated with low adherence to diet in diabetic patients (Ranasinghe et al, 2015;Cheng et al, 2016;Parajuli, Saleh, Thapa & Ali, 2014). Thence, it is important that the information provided to the diabetic patient has clear recommendations for self-care, expressed in a kind of language that the patient may fully understand.…”
Section: Discussionsupporting
confidence: 90%
“…Thence, it is important that the information provided to the diabetic patient has clear recommendations for self-care, expressed in a kind of language that the patient may fully understand. Myths or erroneous beliefs regarding self-care may increase due to lack of information, provoking the sensation of being deprived and denied medical recommendations (Cheng et al, 2016). The high prevalence of distress in type 2 diabetes patients compared to general population and its association with self-care suggests the importance of its screening and care in family practice.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al () also reported that self‐efficacy affected glycaemic levels indirectly through the mediation of self‐care behaviours among Chinese patients with type 2 DM. Greater self‐efficacy led to better self‐management and improved glycaemic control (Beard, Clark, Hurel, & Cooke, ; Cheng et al, ). Hence, these studies concluded that self‐efficacy affected glycaemic levels among adults with type 2 DM.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the availability of many primary studies that have investigated the factors associated with glycaemic control among patients with type 1 or 2 diabetes, attempts to amalgamate these evidences have been methodologically limited. According to a preliminary literature review (Ahola & Groop, ; Cattaneo & Chapman, ; Cheng et al, ; Cheng, Wu, Dawkes, Lim, & Wang, ; Ho, Berggren, & Dahlborg‐Lyckhage, ; Peyrot et al, ; Strychar, Elisha, & Schmitz, ), 10 factors (age, ethnicity, socio‐economic status, duration of disease, medication usage, comorbidity, body mass index, diet knowledge, self‐efficacy and level of empowerment) were proposed as the influencing factors. The systematic literature review sought to provide a robust review of the evidence to explore these influencing factors on glycaemic control in patients with DM.…”
Section: Introductionmentioning
confidence: 99%
“…Aljabri reported that only 9.5% of patients with type I diabetes in Jeddah achieved glycemic control (19), while another study found that10.5% of participants achieved glycemic control (13). Worldwide, comparable findings have been reported in both developed and developing countries, with up to38.7% of patients achieving optimal glycemic control, with some variation between different populations and settings (22,24,26,(42)(43)(44)(45)(46). Consistent with our findings, a range of demographic and clinical factors affect glycemic control, with varying levels of significance.…”
mentioning
confidence: 84%